Restorative Justice in Terrorist Victimisations: Comparative Implications : Introduction = Justicia Restaurativa en el Caso de Victimizaciones Terroristas : Implicaciones Comparativas : Introducción - Varona, Gema (Oñati Socio-Legal Series, 2014)
This issue is focused on the application of restorative justice to terrorist victimisations. Both concepts (restorative justice and terrorist victimisations) are controversial ones in social science and society. We decided to approach them from a concrete programme on restorative encounters developed in the Basque Country in 2011 and 2012. This programme targeted ex-members of ETA, and direct and indirect victims.